2016
DOI: 10.3390/app6080207
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3D Analytical Scattering Model for Air-to-Ground Fading Channels

Abstract: A geometry-based three-dimensional (3D) novel stochastic channel model for air-to-ground (A2G) and ground-to-air (G2A) radio propagation environments is proposed. The vicinity of a ground station (GS) is modelled as surrounded by effective scattering points; whereas the elevated air station's (AS) vicinity is modelled as a scattering-free region. Characterization of the Doppler spectrum, dispersion in the angular domain and second order fading statistics of the A2G/G2A radio communication channels is presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Our theoretical models were verified using measurement data for both V2V in [25], [26] and A2A in [27] and [28]. Similar modeling was applied in [29]- [31] for air-to-ground (A2G) channels.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our theoretical models were verified using measurement data for both V2V in [25], [26] and A2A in [27] and [28]. Similar modeling was applied in [29]- [31] for air-to-ground (A2G) channels.…”
Section: Introductionmentioning
confidence: 80%
“…The highest exponent of variable η is four, which means the resulting curve can have a maximum of four solutions of (31) for a fixed Doppler frequency f d according to Bézout's theorem [41]. The curve C(f d , η) is given by the following expression in (31).…”
Section: Algebraic Analysis Of the Doppler Pdf Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…A SOFS-based analysis of channel simulators implementing Nakagami fading is presented in [20]. A detailed analysis on characterization of angular spread and SOFS of air-to-ground and different outdoor land-mobile radio communication channels for both empirical and geometric channel models is conducted in [21][22][23][24][25]. A study conducted in [26], presents an analysis on SOFS of mmWave communication channel in outdoor radio propagation environment at 28 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], [25], the authors analyzed the influence of azimuth angle of arrival (AAOA) and elevation angle of arrival (EAOA) on the space-time correlation characteristics of a cylinder GBSM UAV channel model, but the analysis of LCR and AFD was missing in these articles. Based on the sphere GBSM channel model, the authors in [26] derived the expressions of second-order statistical properties, which showed LCR was positively correlated with the carrier frequency. In [27], a 3D cylinder GBSM for UAV channels was proposed and the influence of the Rice factor, angle of arrival (AOA), and angle of departure (AOD) on the LCR and AFD was investigated.…”
mentioning
confidence: 99%